2017
DOI: 10.1111/all.13366
|View full text |Cite
|
Sign up to set email alerts
|

Identification of alpha‐gal sensitivity in patients with a diagnosis of idiopathic anaphylaxis

Abstract: IgE antibodies (Ab) specific to galactose-α-1,3-galactose (alpha-gal) are responsible for a delayed form of anaphylaxis that occurs 3-6 hours after red meat ingestion. In a unique prospective study of seventy participants referred with a diagnosis of idiopathic anaphylaxis (IA), six (9%) were found to have IgE to alpha-gal. Upon institution of a diet free of red meat, all patients had no further episodes of anaphylaxis. Two of these individuals had indolent systemic mastocytosis (ISM). Those with ISM had more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 19 publications
(27 reference statements)
1
30
0
3
Order By: Relevance
“…More recently, van Nunen, Commins and others [18][19][20][21][22][23][24] have described a unique population with high titers of anti-gal IgE. Anti-gal IgE develops in a subset of people after an index exposure to gal.…”
Section: Prevalence Of Ige Anti-gal Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, van Nunen, Commins and others [18][19][20][21][22][23][24] have described a unique population with high titers of anti-gal IgE. Anti-gal IgE develops in a subset of people after an index exposure to gal.…”
Section: Prevalence Of Ige Anti-gal Antibodiesmentioning
confidence: 99%
“…The National Institute of Health (NIH) recently highlighted AGS and noted that it is often unrecognized or misdiagnosed 32 . For AGS patients, a tick bite can lead to a hypersensitivity reaction that characteristically manifests as anaphylaxis three to six hours after consumption of mammalian meat products, even in patients who previously tolerated red meat for their entire lives 20,22,33 .…”
Section: Prevalence Of Ige Anti-gal Antibodiesmentioning
confidence: 99%
“…Recently, it has been suggested that α‐gal might be also present in other animal species known to feed parasitically on mammals, and in particular, chiggers (mites of the Trombiculidae family at their larval stage) have been reported to be associated with sensitization to α‐gal and delayed allergy to red meat . Carter et al described, in a prospective study of 70 patients referred with a diagnosis of IA, six cases (9%) with sIgE to α‐gal. Two of these six patients experienced more severe clinical symptoms with a higher baseline serum tryptase and were subsequently found to have indolent systemic mastocytosis.…”
Section: Diagnostic Considerationsmentioning
confidence: 99%
“…Recently, it has been suggested that α-gal might be also present in other animal species known to feed parasitically on mammals, and in particular, chiggers (mites of the Trombiculidae family at their larval stage) have been reported to be associated with sensitization to α-gal and delayed allergy to red meat. 44 Carter et al 45…”
Section: Cofactor-dependent Anaphylaxismentioning
confidence: 99%
“…These patients did not experience any further anaphylactic episodes when red meat was removed from their diet. 26 In 131 participants, who reported adverse reactions to meat, and 26 control subjects, levels of alpha-gal sensitization correlate with high risk of red meat allergy. 27 Cutoff values are described for levels of sensitization to alpha-gal IgE and for the alpha-gal:total IgE ratio that is highly likely to result in clinically significant red meat allergy.…”
Section: Food Allerg En Smentioning
confidence: 99%